Internalisasi Karakter Tanggung Jawab Anak Usia Dini Melalui Pembiasaan Kegiatan Harian di TK Plus Usman Al- Farsy - Dewi Pusparini; Ismatud Diniyah; Wardatul Hamro’; Nawal Widad Ramadani; Lin Istianah (Institut Agama Islam Negeri Madura, 2026)
The most effective way for schools to foster early childhood character development is through habituation activities, which represent the initial stage in shaping children’s character. Children’s perceptions and behaviors can develop and change through continuous stimulation. This study aims to examine how habituation activities support the internalization of children’s character. The research employed a descriptive qualitative method involving 25 group B students at TK Plus Usman Al-Farsy, along with one principal and one assistant teacher as supporting informants. The study was conducted during the first semester of 2025 and lasted for one month. Data were collected through documentation, interviews, and observations, and were analyzed using the Miles and Huberman interactive model. The findings indicate that character internalization was fostered through habitual practices such as cleaning up toys, storing personal belongings, and lining up before and after activities. Consistent implementation, parental support, and teacher role modeling were key contributing factors. This study provides a comprehensive understanding of the processes, stages, and components influencing the successful internalization of responsibility character in early childhood education institutions.